COMPARISON OF THE TRIGLYCERIDE CONTENT OF SEA BUCKTHORN OIL OF THE ALTAI TERRITORY BY DIFFERENTIAL SCANNING CALORIMETRY - Goremykina N.V.; Vereshchagin A.L.; Bychin N.V.; Koshelev Y.A. (Техника и технология пищевых производств)
The melting curves of sea buckthorn oil samples of some producers in the Altai Territory were investigated by differential scanning calorimetry (DSE). Comparison of the data of high-temperature gas chromatography and differential scanning calorimetry showed that melting of the main unsaturated triglycerides of sea buckthorn oil namely tripalmitin and tripalmitolein comply with a maximum endoeffect in the range of 0 С and that of major limiting triglycerides – tripalmitates – in the range of 10–15 С. The possibility to identify the origin of the samples of sea buckthorn oil by DSC is shown.